A Brief Assessment of Body Image Perception: Norm Values and Factorial Structure of the Short Version of the FKB-20 - Schmalbach, Ileana; Schmalbach, Bjarne; Zenger, Markus; Berth, Hendrik; Albani, Cornelia; Petrowski, Katja; Brähler, Elmar (Frontiers in Psychology, 2020)
The Body Image Questionnaire-20 (FKB-20) is one of the most applied self-report measures in the context of body image assessment in German-speaking regions. A version of the FKB-20 capturing an ideal concept of body image is also available. A special property of the scale is its high sensitivity for individuals suffering from anorexia nervosa. The present research provided a short version of this scale (for both variants) and examined its validity in a representative sample (N = 2,347) of the German population. We utilized factor analysis methods to identify the optimal short scale of the measure, finding excellent model fit and reliability for a two-factor model (FKB-6) for both real and ideal body image. Both versions of the FKB-6 can be considered invariant across sex and age groups. Good reliability indices were shown for both versions of the FKB-6. The reliability indices were similar to those mentioned in previous studies. Our study also revealed, that large discrepancies between the real and an ideal body image are correlated with somatic and body dysmorphic symptoms. Finally, we provided norm values for comparisons of individual scores with the general population. The FKB-6 is a valid and a reliable measure that economizes assessments by clinicians and researchers.